Drought Stress Predominantly Endures Arabidopsis thaliana to Pseudomonas syringae Infection - Gupta, Aarti; Dixit, Sandeep K.; Senthil-Kumar, Muthappa (Frontiers in Plant Science, 2016)
Plant responses to a combination of drought and bacterial pathogen infection, an agronomically important and altogether a new stress, are not well studied. While occurring concurrently, these two stresses can lead to synergistic or antagonistic effects on plants due to stress-interaction. It is reported that plant responses to the stress combinations consist of both strategies unique to combined stress and those shared between combined and individual stresses. However, the combined stress response mechanisms governing stress interaction and net impact are largely unknown. In order to study these adaptive strategies, an accurate and convenient methodology is lacking even in model plants like Arabidopsis thaliana. The gradual nature of drought stress imposition protocol poses a hindrance in simultaneously applying pathogen infection under laboratory conditions to achieve combined stress. In present study we aimed to establish systematic combined stress protocol and to study physiological responses of the plants to various degrees of combined stress. Here, we have comprehensively studied the impact of combined drought and Pseudomonas syringae pv. tomato DC3000 infection on A. thaliana. Further, by employing different permutations of drought and pathogen stress intensities, an attempt was made to dissect the contribution of each individual stress effects during their concurrence. We hereby present two main aspects of combined stress viz., stress interaction and net impact of the stress on plants. Mainly, this study establishes a systematic protocol to assess the impact of combined drought and bacterial pathogen stress. It was observed that as a result of net impact, some physiological responses under combined stress are tailored when compared to the plants exposed to individual stresses. We also infer that plant responses under combined stress in this study are predominantly influenced by the drought stress. Our results show that pathogen induced disease symptoms were ameliorated by drought stress in combined stressed plants. Combined stressed plants also displayed reduced ROS generation and declined cell death which could be attributed to activation of effective basal defence responses. We hypothesize a model on ABA mediated gene regulation to partly explain the possible mechanistic basis for reduced in planta bacterial numbers under combined stress over individual pathogen